PERANCANGAN KANTIN BERSAMA UNIVERSITAS LAMBUNG MANGKURAT BANJARBARU - Adilla Rizqi Ramadhani; Yuswinda Febrita; Irwan Yudha Hadinata (UNIVERSITAS LAMBUNG MANGKURAT, 2025)
The Government Regulation of the Republic of Indonesia Number 19 of 2005 mandates that every educational institution must provide infrastructure, including a canteen. Although each faculty at Lambung Mangkurat University Banjarbaru already has a canteen, its function does not align with the standards set by the Ministry of National Education, which defines a canteen as a place for discussion and waiting during free periods. This is supported by observations, interviews, and questionnaires conducted with canteen stakeholders at Lambung Mangkurat University Banjarbaru. Based on these findings, the problem raised is: